Evaluación del riesgo ergonómico para la prevención de trastornos músculos esqueléticos en el área de Planeamiento Urbano y Ordenamiento Territorial en el GAD Municipal Quevedo. - Ortega Vera, Rogelio Javier (2018)
The purpose of the present study is to evaluate the ergonomic risks to improve the work performance in the area of urban planning and territorial ordering of the Municipal decentralized government Quevedo, contributing the outstanding Performance and efficiency in each of their work activities. In the research was analyzed, each of the jobs with which the GAD Municipal Quevedo, through the lifting of administrative information.The ICONTEC GTC 45 risk matrix was obtained, identifying the ergonomic risk factors for each of the jobs as forced postures (standing, seated). Reaching the conclusion, applying the specific ergonomic evaluation methods such as: REBA, Check List method okra, and data visualization screens have resulted in levels of risks low, medium, high by forced postures, movements and data display screens (PVD), which leads to improved jobs. This was the culmination of this study, guaranteeing a safe and comfortable working environment of the workers in the area of urban planning and territorial ordering of the Municipal decentralized autonomous government Quevedo, also This need raises a training program, the implementation of active pauses program to improve the performance of workers in their jobs and a prevention program that allows to control the risk factors ergonomics by Forced postures and repetitive movements, prevailing training programs in the source of danger, in the transmission medium and finally in the person. Keywords: Ergonomics, skeletal muscle disorders, ergonomic risks, evaluation methods